A new puzzle about belief and credence. Issue 2 (17th February 2019) - Moon, Andrew
ABSTRACT: I present a puzzle about belief and credence, which takes the form of three independently supported views that are mutually inconsistent. The first is the view that S has a modal belief that p (e.g., S believes that probably- p ) if and only if S has a corresponding credence that p . The second is the view that S believes that p only if S has some credence that p . The third is the view that, possibly, S believes that p without a modal belief that p . [Word Count: 85]